Effect of Ultrasonic Exposure on the Efficiency of De-Oiling Fluid Lecithins - Ekaterina V. Lisovaya; Elena P. Viktorova; Anastasia V. Sverdlichenko; Mariet R. Zhane (Техника и технология пищевых производств)
De-oiling fluid lecithin is a resource- and energy-intensive process that provides a phospholipid isolate with a high content of phospholipids. Ultrasonic exposure is one of the most effective and easy-to-implement physical methods that intensify this chemical-technological procedure. This article describes the effect of ultrasonic exposure on the efficiency of de-oiling fluid lecithins. The research featured soy lecithin (fluid, partially de-oiled, phospholipid isolate). The de-oiling process involved acetone as a solvent and included three 10-min stages at a temperature of 40°C. The ratio of lecithin:acetone (by weight) was as follows: stage I – 1:7, stage II – 1:6, stage III – 1:5. The systems of fluid lecithin – acetone and partially de-oiled lecithin – acetone underwent ultrasonic treatment during the de-oiling process at different specific power and exposure time. As a result of filtration, phases separated into an acetone solution of neutral lipids and phospholipids. The phospholipid isolate was dried in a vacuum oven at 5 kPa and 40°C. Each stage ended with the following measurements: the content of phospholipids in partially de-oiled lecithins, the content of phospholipids in the phospholipid isolate, and the extraction degree of neutral lipids after distilling the solvent from the acetone miscella. The specific power in the lecithin – acetone system was 0.28 W/cm3 at de-oiling stage I and 0.36 W/cm3 at stages II and III. Three minutes of ultrasonic exposure at stages I and II and two minutes at stage III reduced the acetone consumption by 1.2 times. The resulting phospholipid isolate yielded by 3.3% more phospholipids than the control sample, which presupposed no ultrasonic treatment. Ultrasonic exposure proved to be an effective and solvent-saving three-stage method that intensified the process of de-oiling fluid soy lecithin. The study specified the optimal technological modes for obtaining a phospholipid isolate with a high content of phospholipids (98.6%), which can be recommended as a food additive.